New evidence on the protector effect of weight gain in retinopathy of prematurity - María J. Chaves-Samaniego; María C. Chaves-Samaniego; Antonio Muñoz Hoyos; José L. García Serrano (Elsevier, 2021)
Introduction: Retinopathy of prematurity (ROP) is characterised by insufficient vascular development in the retina, and requires early treatment to avoid visual disability in severe cases. ROP is currently the second leading cause of preventable child blindness in the world. Patients and methods: This was an observational, retrospective, case-control study including 233 preterm infants examined between 1999 and 2019. Results: Postnatal weight gain in the first 4 weeks of life, birth weight, gestational age, mechanical ventilation, transfusion, presence of sepsis, persistence of arterial ductus, necrotising enterocolitis, intraventricular haemorrhage, or periventricular leukomalacia were found to be significantly different between the ROP groups requiring and not requiring treatment. The mean postnatal weight gain in the ROP group not requiring treatment was 12.75 ± 5.99 g/day, whereas it was 9.50 ± 5.45 g/day in the ROP group requiring treatment. The risk of developing ROP that required treatment decreased with an increase in weight gain. The risk reduction was 2.76%-8.35% in preterm infants gaining 10 g/day, and 7.17%-12.76% in infants gaining 20 g/day. Conclusions: The risk of developing ROP requiring treatment decreased with increasing weight gain in the first 4 weeks of life. This was applicable in infants with postnatal weight gain ≥14 g/day. However, gestational age, birth weight, time of mechanical ventilation, and comorbidity should be taken into account when evaluating the risk of ROP requiring treatment. Resumen: Introducción: La retinopatía del prematuro (ROP) se caracteriza por el desarrollo vascular insuficiente en la retina que, en los casos severos precisa tratamiento precoz para evitar secuelas visuales. Es actualmente la segunda causa mundial de ceguera infantil prevenible. Pacientes y métodos: Estudio observacional, retrospectivo, de casos-controles sobre 233 recién nacidos prematuros explorados entre 1999−2019. Resultados: La ganancia de peso postnatal en las primeras 4 semanas, el peso al nacer, la edad gestacional, la ventilación mecánica, las transfusiones recibidas y la presencia de sepsis, ductus arteriovenoso persistente, enterocolitis necrotizante, hemorragia intraventricular o leucomalacia periventricular, mostraron diferencias significativas entre el grupo de ROP no susceptible de tratamiento frente al grupo candidato a tratamiento. La ganancia ponderal media fue 12,75 ± 5,99 g/día en el grupo no susceptible de tratamiento y 9,50 ± 5,45 g/día en el susceptible de tratamiento. El riesgo de ROP candidata a tratamiento se redujo progresivamente con el aumento de ganancia ponderal. La reducción del riesgo fue de 2,76-8,35% en ganancias de 10 g/día, y alcanza el 7,17-12,76% en ganancias de 20 g/día. Conclusiones: El riesgo de presentar ROP severa candidata a tratamiento disminuye con el aumento de la ganancia de peso postnatal en las primeras 4 semanas. Esta relación se mantiene en ganancias de peso >14 g/día. Sin embargo, se deben tener en cuenta la edad gestacional y peso al nacer del recién nacido, la duración de la ventilación mecánica y su comorbilidad para la evaluación global del riesgo de ROP que precisa tratamiento.